Legal foundations of cooperation between the Republic of Kazakhstan and foreign states in the military sphere: issues military policy and service - Botagarin, R.B.; Musin, K.S. (Bulletin of the Karaganda University “Law Series”, 2025)
This article examines the current state of cooperation between the Republic of Kazakhstan and various foreign nations in the military domain. According to the authors, in recent years, amid global militarypolitical instability, the primary condition for mitigating adverse consequences is the continued collaboration in the military sector. The study analyzes measures taken to ensure military security, as well as the distinctive features of military activity directions. The objective of this research is to explore the legal foundations of the Republic of Kazakhstan’s military cooperation with international organizations, the Republic of Turkey, and the Russian Federation. During the research, a legal analysis of agreements in the military domain was conducted, and comparative-legal methods were applied. The research is grounded in a range of normative sources, including the Constitution of the Republic of Kazakhstan, the country’s military doctrines, agreements on military cooperation with the Republic of Turkey, military cooperation plans, and various other legal instruments that govern military collaboration. The authors conclude that the establishment of military cooperation with neighboring countries to ensure peaceful coexistence is one of the most crucial functions of any state in guaranteeing military security.